Carbon Dioxide Absorption Using Monoethanolamine, Piperazine and N-Metil Solvents Under Counter Current Regime in Packed Column Reactor - Gul, Ayse; Baris, Mesut; Un, Umran Tezcan (Elsevier Sci Ltd, 2024)
In this research the carbon dioxide absorption using Monoethanolamine (MEA), Piperazine (PZ) and N-Metil-2-pirolidon (NMP) solvents and their different blends (MEA/NMP, PZ/NMP, MEA/PZ) in packed column reactor filled with Raschig rings was investigated and compared for efficient carbon dioxide absorption. The process was followed in a countercurrent regime under a liquid flow rate of 200 mL/min, gas flow rate of 2.5 L/min, and CO2 concentration of 50,000 ppm. Carbon dioxide removal efficiency (%), absorption capacity (mol CO2/mol solvent), overall mass transfer coefficient (1/min) and absorption rate (mol/l.s) were monitored. The highest obtained values for carbon dioxide removal efficiency, absorption capacity and overall mass transfer coefficient were 57.5%, 0.148 mol CO2/mol solvent and 2.178 min-1 respectivelly when 0.03 M MEA/0.07 M PZ in a hybrid system was used. It was concluded that PZ blends with MEA were successful absorbent as the organic physical solvent whereas NMP didn't show improving effect in blends with MEA on the absorption efficiency.
Baris, Mesut/0000-0002-7924-8396; Gul, Ayse/0000-0002-2305-6408;
Keywords: CO2 Absorption; Counter Current Packed Bed Reactor; Hybrid Absorbent Blends; Raschig Ring; Monoethanolamine (Mea); Piperazine (Pz); N-Metil-2-Pirolidon (Nmp); CO2 Absorption